PENGARUH PENERAPAN KAIZEN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI DEPARTEMEN CUSTOMER SERVICE PT BCA FINANCE - Mochamad Soelton; Rizky Andrafiana Rahmi (Universitas Mercu Buana, 2016)
he research is to determine the affect of Kaizen and work dicipline to employee performance. Theobject for this research is employee of Customer Service Department in PT BCA Finance. The research wasdone to 72 respondents consist of staff and team leader. The research using quantitative-descriptiveapproach with Non Probability Sampling method using Convenience Sampling. Data collected byquestionnaire and the data analyzed using multiple linier regressio. Data processing for statistical tests performed by software SPSS version 20.The results of the research indicate that in partially, Kaizen has not significant influence on employee performance but work dicipline has significant influence on employee performance of Customer ServiceDepartment in PT BCA Finance